The Political Communication Style of Gibran Toward First-Time Generation Z Voters on Social Media: A Framing Analysis of Diction Aligned with Youth Preferences - Ade Rachmat Yudiyanto; Hasrat Efendi Samosir; Katimin (Faculty of Law, Universitas Pekalongan, 2025)
This research aims to analyze Gibran Rakabuming Raka's political communication style to Generation Z first-time voters on social media with a framing analysis approach. As a young politician, Gibran utilizes platforms such as TikTok and Instagram to form a more casual, familiar, and relatable political image for young people. Through the use of popular diction such as